System of autonomous activities as contribution to speaking skill development of third-semester students from pedagogy of national and foreign languages degree - Ramos Jaramillo, Alex Xavier (Machala: Universidad Técnica de Machala, 2024)
The aim of the present study is to contribute to the development of oral expression in English of students in the third semester of the Pedagogy of National and Foreign Languages degree at the Universidad Técnica de Machala during the regular academic period 2024-1. The difficulties that appear during the production of oral expression and that affect the process of the students of English as a foreign language can be related to the lack of knowledge of adequate strategies and resources, which are vast and easily accessible nowadays. The proposal implemented in the study group of 28 students was a system of activities based on the autonomous learning approach. Theoretical methods such as hypothetical-deductive and systemic and empirical methods such as measurement, non-participant observation and pedagogical testing were used in order to collect, measure and analyse the relevant research data. This allowed us to corroborate that the implemented proposal contributes significantly to the development of this skill of the study group. It is recommended that the proposed system of autonomous activities be applied to larger populations belonging to similar third-level studies.
La ejecución del presente estudio tiene como objetivo contribuir al desarrollo de la expresión oral en inglés de los estudiantes del tercer semestre de la carrera de Pedagogía de los Idiomas Nacionales y Extranjeros en la Universidad Técnica de Machala durante el periodo académico ordinario 2024-1. Las dificultades que aparecen durante la producción de la expresión oral y que afectan el proceso de los estudiantes de inglés como idioma extranjero pueden estar relacionadas al desconocimiento de estrategias y recursos adecuados, los cuales son vastos y de fácil acceso hoy en día. La propuesta implementada en el grupo de estudio conformado por 28 estudiantes fué un sistema de actividades basado en el enfoque del aprendizaje autónomo. Se usaron métodos teóricos como el hipotético-deductivo y el sistémico y métodos empíricos como la medición, la observación no participante y la prueba pedagógica con el fin de recopilar, medir y analizar los datos relevantes de la investigación. Lo cual permitió corroborar que la propuesta implementada contribuye significativamente al desarrollo de esta habilidad del grupo de estudio. Se recomienda aplicar el sistema de actividades propuesto en poblaciones más grandes y que se encuentren cursando estudios similares de tercer nivel.
Keywords: LEARNING-TEACHING PROCESS; SPEAKING SKILL; AUTONOMOUS LEARNING; LEARNER AUTONOMY